Biological Maturity And Its Relationship To Some Anthropometric Measurements And Physical Performance In 15-16 Year Old Male Cycling Riders - Sadouki, Kamel (sports creativity, 2025)
The aims of this study are to Determine differences in selected anthropometric measurements and physical performance between the levels of biological maturation of a group of 15-16 year-old riders. And estimate the contribution of biological age on riders’ physical performance. Thirty male cycling riders (Age = 15,8±0,67 years), from the U17 category, are participated in the study. Riders were sub-divided into three biological maturation groups, early maturing (n=8), average maturing (n=8), and late maturing (n=14), using the WUTSCHERK’s anthropometric method. All anthropometric measurements and assessments (Peak power output test and field tests), were performed. The present study shows that early maturing riders are taller and heavier (p<0,001), and performed better in physical tests that required, power, speed, and resistance (P<0,01).